The impact of the duration of the palliative care period on cancer patients with regard to the use of hospital services and the place of death: a retrospective cohort study - Outi M. Hirvonen; Riikka-Leena Leskelä; Lotta Grönholm; Olli Haltia; Samuli Voltti; Kristiina Tyynelä-Korhonen; Eeva K. Rahko; Juho T. Lehto; Tiina Saarto (BMC, 2025)
Background: In order to avoid unnecessary use of hospital services at the end-of-life, palliative care should be initiated early enough in order to have sufficient time to initiate and carry out good quality advance care planning (ACP). This single center study assesses the impact of the PC decision and its timing on the use of hospital services at EOL and the place of death.
Methods: A randomly chosen cohort of 992 cancer patients treated in a tertiary hospital between Jan 2013 -Dec 2014, who were deceased by the end of 2014, were selected from the total number of 2737 identified from the hospital database. The PC decision (the decision to terminate life-prolonging anticancer treatments and focus on symptom centered palliative care) and use of PC unit services were studied in relation to emergency department (ED) visits, hospital inpatient days and place of death.
Results: A PC decision was defined for 82% of the patients and 37% visited a PC unit. The earlier the PC decision was made, the more often patients had an appointment at the PC unit (> 180 days prior to death 72% and < 14 days 10%). The number of ED visits and inpatient days were highest for patients with no PC decision and lowest for patients with both a PC decision and an PC unit appointment (60 days before death ED visits 1.3 vs 0.8 and inpatient days 9.9 vs 2.9 respectively, p < 0.01). Patients with no PC decision died more often in secondary/tertiary hospitals (28% vs. 19% with a PC decision, and 6% with a decision and an appointment to a PC unit).
Conclusions: The PC decision to initiate a palliative goal for the treatment had a distinct impact on the use of hospital services at the EOL. Contact with a PC unit further increased the likelihood of EOL care at primary care.